UPAYA GURU BIMBINGAN KONSELING DALAM MENCEGAH PERILAKU BULLYING SISWA DI SMAN 17 LUWU - Subekti Masri; Teguh Arafah Julianto; Sitti Aisyah; Kasmi Kasmi (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2023)
Abstract This research aims to find out 1) The causes of bullying behavior at SMAN 17 Luwu, 2) The impact of bullying behavior on students who are victims of bullying at SMAN 17 Luwu 3) The efforts of Guidance Counseling teachers in preventing student bullying behavior at SMAN 17 Luwu. This research is a qualitative descriptive research using a case study method. The informants for this research were guidance and counseling teachers, student affairs teachers, homeroom teachers, perpetrators and victims of bullying. The data collection methods used were observation, interviews and documentation. Analysis of research data is by using data reduction, data presentation and drawing conclusions. The results of this study show that there are 4 factors that cause bullying behavior, namely family factors, peers, electronic media and the school environment. The negative impact of bullying behavior on students who are victims of bullying is that children will close themselves off or be shy, lack self-confidence and children feel afraid of going to school. Several efforts have been made by guidance and counseling teachers at SMAN 17 Luwu to prevent bullying behavior, namely forming the value of friendship. motivating students to have a social spirit, be active and achieve, build effective communication, provide positive education to students regarding the impacts of bullying behavior. Keywords: The efforts of BK teachers, Bullying, SMAN 17 Luwu